Popular Heritage in Life Cycle Habits (Pregnancy and Childbirth) Anthropological study in the Coastal Village of Balloran - Kharma, Eva (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The importance of the study of cultural heritage in the customs of pregnancy and childbirth, is that it has been and continues to be an integral part of the cultural heritage elements of human societies, with its meanings and important social functions that contribute to the realization of the requirements of social interaction and solidarity and especially the members of rural communities. The study shows that there have been major shifts in traditional birth and birth habits in the village community that we are studying, namely, the coastal village of Balloran. As an inevitable result dictated by the processes of social acculturation and interaction, which paved the way for them the revolution of communication and informatics, taking the habits of pregnancy and childbirth and therefore care for the baby is changing. In keeping with the requirements of the age of speed in change and It is clear that many of the traditional cultural values that were prevalent in the past have disappeared, while new cultural patterns have emerged, characterized by the lack of cultural and cultural cohesion that are consistent with the current era, as well as the persistence of some other cultural values and coexistence alongside modern values.